Chemical structure of hydrolysates of cereulide and their time course profile. Issue 9 (1st May 2020) - Naka, Toshihito; Takaki, Yuka; Hattori, Yoshihide; Takenaka, Hiroshi; Ohta, Yoichiro; Kirihata, Mitsunori; Tanimori, Shinji
Graphical abstract: Abstract: Hydrolysates of an emetic toxin cereulide were found in the broth of Bacillus cereus . The ester cleaved depsipeptides of cereulide were synthesized using liquid phase fragment condensation method starting from commercially available amino acids. The chemical structure of hydrolysates was verified tetradepsipeptide l - O -Val-l -Val-D- O -Leu-d -Ala and dodecadepsipeptide (D- O -Leu-d -Ala-l - O -Val-l -Val)3 using LC-TOFMS. Quantitative analysis of cereulide in the broth revealed production of cereulide in the stationary phase and decomposition in the death phase. The increase in tetradepsipeptide continued after the stationary phase until decomposition occurred.